Smart Wireless Attendance System - Shivanand C, Kohalli; Kulkarni, Ramchandra; Salimath, Mahantesh; Hegde, Mahesh; Hongal, Rohini (International Journal of Computer Sciences and Engineering, 2025)
This paper describes a method for attendance monitoring through a wireless network of smart devices (IoT). Today, IoT is enabled by the latest developments in RFID, smart sensors, communication technologies, and Internet protocols. IoT is expected to bridge diverse technologies to enable new applications by connecting physical objects together in support of intelligent decision making. The basic premise here is to have smart sensors collaborate directly without human involvement to deliver a new class of application. Compared with the existing technology where local sensors are deployed to monitor attendance OR where often the technology is barely used requiring human intervention, our intention here is to provide a hassle free system which is mobile and requires no human intervention (except for the unavoidable initial set-up). Not only our solution eradicates the burden on human resource but also, provides a convenient way to interact by hosting a web-page for viewing the attendance report of every student.